2005
DOI: 10.2174/157339905774574383
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Thiamine (Vitamin B1) in Diabetic Complications

Abstract: Accumulation of triosephosphates arising from high cytosolic glucose concentrations in hyperglycemia is one likely or potential trigger for biochemical dysfunction leading to the development of diabetic complications. This may be prevented by disposal of excess triosephosphates via the reductive pentosephosphate pathway. This pathway is impaired in experimental and clinical diabetes by mild thiamine deficiency. The expression and activity of the thiamine-dependent enzyme, transketolase--the pacemaking enzyme o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 55 publications
(72 reference statements)
2
105
0
6
Order By: Relevance
“…Increased tissue content of AGEs in diabetes leads to impairment of protein function, linked to vascular cell detachment and anoikis [16,17], oxidative stress [18], low-grade inflammation [18,19] and other cell dysfunctions implicated in the development of microvascular complications [20]. Thiamine and benfotiamine proba- Data are means±SD; units are mmol/mol lysine for FL, CML and CEL and mmol/mol arginine for G-H1, MG-H1 and 3DG-H Rat study group key as in Table 1 *p<0.05, **p<0.01 and ***p<0.001 with respect to normal control † p<0.05, † † p<0.01 † † † p<0.001 with respect to diabetic controls bly decrease AGE and oxidation and nitration adduct formation by increasing transketolase expression and activity in tissues [3,4,21]; this counters metabolic dysfunction and oxidative stress in hyperglycaemia, maintains antioxidant and dicarbonyl-metabolising enzyme activities and thereby prevents protein damage [2]. This is the first application of quantitative 'gold standard' stable isotopic dilution analysis LC-MS/MS to quantify a comprehensive range of glycation, oxidation and nitration adducts in tissues, plasma and urine in experimental diabetes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Increased tissue content of AGEs in diabetes leads to impairment of protein function, linked to vascular cell detachment and anoikis [16,17], oxidative stress [18], low-grade inflammation [18,19] and other cell dysfunctions implicated in the development of microvascular complications [20]. Thiamine and benfotiamine proba- Data are means±SD; units are mmol/mol lysine for FL, CML and CEL and mmol/mol arginine for G-H1, MG-H1 and 3DG-H Rat study group key as in Table 1 *p<0.05, **p<0.01 and ***p<0.001 with respect to normal control † p<0.05, † † p<0.01 † † † p<0.001 with respect to diabetic controls bly decrease AGE and oxidation and nitration adduct formation by increasing transketolase expression and activity in tissues [3,4,21]; this counters metabolic dysfunction and oxidative stress in hyperglycaemia, maintains antioxidant and dicarbonyl-metabolising enzyme activities and thereby prevents protein damage [2]. This is the first application of quantitative 'gold standard' stable isotopic dilution analysis LC-MS/MS to quantify a comprehensive range of glycation, oxidation and nitration adducts in tissues, plasma and urine in experimental diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…This is probably related to the thiol intermediate formed by thioester hydrolysis of benfotiamine [2]. This may participate in thiol/disulfide exchange reactions, preserve thiol status and thereby prevent formation of MetSO and maintain levels of thioredoxin cofactor for MetSO reductase [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 The latter is associated with stimulation of mitochondrial dysfunction and formation of oxidative stress, increased diacylglycerol formation and activation of protein kinase C, activation of the hexosamine pathway and increased formation of methylglyoxal and AGEs. 36 Further disturbance of thiamine metabolism in renal failure occurs by decreased expression of thiamine transporters in small intestine, heart, liver and brain and likely decreased availability of thiamine at these sites. 37 Herein we showed that incubation of red blood cells from HD patients ex vivo with thiamine restored normal levels of transketolase activity and R5P concentration, consistent with correction of impaired pentose pathway activity.…”
mentioning
confidence: 99%